Community Empowerment Through Kimbal Cakalang Rindu Products in Improving the Economy of the Local Community - Azisi Azisi; Fathor Rosi (Universitas Nurul Jadid, 2025)
The development of skipjack chili sauce products has proven to be an innovative solution for improving the economy of coastal communities, particularly in Gebangan Village. This study employs the Participatory Action Research (PAR) approach, engaging the community in the entire process of production, marketing, and evaluation. The findings indicate that the implementation of digital marketing strategies via WhatsApp, Instagram, and TikTok increased sales by 40% within the first two months. Additionally, the average monthly income of participants increased by IDR 750,000 - IDR 1,200,000, and 15 housewives, who previously had no steady income, are now actively involved in the production and marketing of skipjack chili sauce. In terms of product quality, using glass bottles for packaging extended the product's shelf life to 45 days under cold storage conditions. However, challenges remain in digital literacy, limited access to capital, and fluctuations in raw material prices. Thus, further training in business management and digital marketing strategies is necessary to ensure the sustainability of this local product-based business. This research contributes to an economic empowerment model based on fishery resources, which can be adapted to other coastal communities.